Cegah Stunting melalui Pendidikan Gizi dan Pelatihan Penyusunan Menu Gizi Seimbang bagi Ibu Balita dan Kader Posyandu - Kosnayani, Ai Sri; Susilowati, Prima Endang; Fikrinisa, Rizka (LPPM STIKes Muhammadiyah Ciamis, 2024)
Introduction: The prevalence of stunting in West Java Province based on data from the 2021 Indonesian Nutritional Status Survey (SSGI) reached 24.5%, above the national average stunting rate of 24.4% and stunting cases in Tasikmalaya City in 2022 were at 14.58% or 6,243. One of the risk factors for stunting is a lack of nutritional intake, especially animal protein. The mother's parenting pattern in providing food is influenced by the mother's knowledge of balanced nutrition rich in animal protein. Providing nutritional counseling using leaflets is expected to increase the mother's knowledge which will lead to a decrease in stunting. Objective: Reducing the incidence of stunting in toddlers in Kota Baru Village, Cibeureum District, Tasikmalaya City by providing nutritional education using counseling methods assisted by leaflets on balanced nutrition rich in animal protein for mothers of toddlers and integrated health post cadres. Method: This public service was conducted by providing nutritional education using counseling methods assisted by leaflets regarding balanced nutrition rich in animal protein for mothers of toddlers and integrated health post cadres. Result: there is an increase in the knowledge of mothers of toddlers regarding balanced nutrition rich in animal protein where the first measurement with an average knowledge score of 9.74 and the second measurement with an average knowledge score of 12.43. The p value = 0.000 indicates a significant difference between the average pre and post test values. Conclusion: Providing nutritional counseling assisted by leaflets about balanced nutrition high in animal protein is effective in increasing mothers' knowledge about balanced nutrition rich in animal protein for toddlers.